Capital-labor substitution, structural change, and growth - Francisco Alvarez-Cuadrado; Ngo Van Long; Markus Poschke (Theoretical Economics, 2017)
There is growing interest in multisector models that combine aggregate balanced growth, consistent with the well known Kaldor facts, with systematic changes in the sectoral allocation of resources, consistent with the Kuznets facts. Although variations in the income elasticity of demand across goods play an important role in initial approaches, recent models stress the role of supply-side factors in this process of structural change, in particular sector-specific technical change and sectoral differences in factor proportions. We explore a general framework that features an additional supply-side mechanism and also encompasses these two known mechanisms. Our model shows that sectoral differences in the degree of capital-labor substitutability-a new mechanism-are a driving force for structural change. When the flexibility to combine capital and labor differs across sectors, a factor rebalancing effect is operative. It tends to make production in the more flexible sector more intensive in the input that becomes more abundant. As a result, growth rates of sectoral capital-labor ratios can differ and, if this effect dominates, shares of each factor used in a given sector can move in different directions. We identify conditions under which this occurs and analyze the dynamics of such a case. We also provide some suggestive evidence consistent with this new mechanism. A quantitative analysis suggests that this channel was an important contributor to structural change out of agriculture in the United States.
Keywords: O30; O40; O41; 330; Capital-labor substitution; balanced growth; structural change